Using of Some Aqueous Plant Extracts in TreatIng the Gold Fishes, Carassius auratus Infected With the Fungus,Saprolegnia sp - Yaseen, A.N. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The gold fishes, Carasusius auratus infected with the fungus, Saprolegnia sp. were treated with different concentrations of Aqueous extracts of coriander , Coriandrun sativum seeds and Henna, Lawsonia inermis leaves by applying the dip method in a water bath for five minutes. The total killing of these fungi was achieved by using 30 % of the C. sativum seeds from Aqueous extract and 40 % of the L. inermis leaves from Aqueous extract. Changes in behaviors of treated fishes, were increased with the increasing concentration for plant extract of C. sativum seeds. It was observed excitation of fishes , crushing with aquaria sides, jumping outside of aquaria, as well as increasing the number opercula movements . While in case of treated fishes with plant extract of L. inermis, it showed normal behaviour in all of the concentrations of the studied extracts.